Area Analysis of Commodity and Contribution of Coffee to Regional Development in Central Aceh Regency - Zikria, Virda (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2020)
Coffee is one of commodities that has important role in the national economy in generating foreign exchange, providing employment and industrial raw materials. This study aims to identify the base areas for coffee production and the role of coffee in supporting regional development in Central Aceh Regency. The data used are secondary data for the time period 2015-2019. The data analysis method used are the location quotient analysis, locality, specialization, basic service ratio analysis and regional multiplier. The results showed that the coffee base areas based on production indicators in Central Aceh Regency were all district in Central Aceh Regency except Silih Nara District. Arabica coffee commodity farming is not localized and concentrated in one particular district but spreads in several districts and does not specialize in coffee commodity farming. Coffee farming is able to support regional development activities in Central Aceh Regency.Keywords: Coffee, Location quotient, Localization, Specialization